PERENCANAAN PUSAT UKM DI PASAR SENI MUSEUM MULAWARMAN TENGGARONG PENEKANAN PADA SIRKULASI RUANG DALAM - Nur Husniah Thamrin; Anna Rulia; Daffa Sega Maulana (Indonesian Society of Applied Science, 2021)
Souvenir center is a place that is sought when someone is visiting a city and wants to buy souvenirs typical of the city. With these souvenirs can be a souvenir for relatives and can also be a memento of the city that was visited. The Art Market is a souvenir shopping center typical of the city of Tenggarong, where the city of Tenggarong is very thick in culture and there are various types of handicrafts that can be used as souvenirs. With the Art Market, it can awaken the economy of the surrounding community because of the existence of Small and Medium Enterprises (SMEs) the results of the Tenggarong handicrafts with high selling value. Inadequate facilities and infrastructure, making the Art Market less well organized. There are no buildings available to be occupied by the sellers of souvenirs, so the sellers make small stalls on the edge of the Mulawarman Tenggarong Museum area. With these problems, the authors design a building that can be a container for sellers souvenirs with a neat layout of space, and also an attraction for visitors who come. By using an emphasis on neo vernacular architectural style, this building will look in accordance with the Mulawarman Museum building